2011
DOI: 10.1016/j.actatropica.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of home-based lymphoedema management in reducing acute attacks in subjects with lymphatic filariasis in Burkina Faso

Abstract: One of the two main goals of the Global Programme to Eliminate Lymphatic Filariasis (LF) is to provide care for those suffering from the devastating clinical manifestations of this filarial infection. Among the 120 million infected people worldwide, up to 16 million have lymphoedema. The WHO strategy for managing lymphoedema is based on rigorous skin hygiene, exercise, antibiotics and antifungals when indicated. The aim is to reduce acute attacks of adenolymphangitis and cellulitis responsible for lymphoedema … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…These findings are consistent with other studies which have also found a decrease in ADLA episodes following enrollment in a lymphedema management program [2], [3], [13], [14], [23], [24]. Other programs have found a similar plateauing of the ADLA rate 3–12 months after beginning lymphedema management [13], [14]. Although our results show a significant decrease in the rate of ADLA episodes over the 2 years since the lymphedema management program was implemented, we recognize that this decrease may be partially influenced by patient receipt of anti-filarial drugs during the two MDAs that took place over the course of the study [21].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings are consistent with other studies which have also found a decrease in ADLA episodes following enrollment in a lymphedema management program [2], [3], [13], [14], [23], [24]. Other programs have found a similar plateauing of the ADLA rate 3–12 months after beginning lymphedema management [13], [14]. Although our results show a significant decrease in the rate of ADLA episodes over the 2 years since the lymphedema management program was implemented, we recognize that this decrease may be partially influenced by patient receipt of anti-filarial drugs during the two MDAs that took place over the course of the study [21].…”
Section: Discussionsupporting
confidence: 92%
“…The rate of ADLA was lowest six months after enrollment, yet a decrease was sustained over the two year period of the study. These findings are consistent with other studies which have also found a decrease in ADLA episodes following enrollment in a lymphedema management program [2], [3], [13], [14], [23], [24]. Other programs have found a similar plateauing of the ADLA rate 3–12 months after beginning lymphedema management [13], [14].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…While previous studies have demonstrated improvements in patient quality of life and a reduction in ADL episodes after beginning lymphedema management, most have assessed patients over relatively short periods of time (≤1 year) and on a smaller scale [14], [15]. The objective of this study, therefore, was to evaluate the longer-term impact of a large-scale, community-based lymphedema management program on perceived disability and productivity among lymphedema patients using a validated disability-assessment tool [16].…”
Section: Introductionmentioning
confidence: 99%